Scientific Publications in International Magazines — Requirement of Science, Time, Ministry or the Rectorate? - Петренко, В. П. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
1